Woodrow Wilson papers - Wilson, Woodrow, 1856-1924.; Wilson, Edith Bolling Galt, 1872-1961.
Personal, family, and official correspondence, drafts and proofs of books, articles, speeches, academic lectures, scrapbooks, shorthand notes, and memorabilia relating chiefly to Wilson's presidential administrations. Includes minutes and other documents on the Paris Peace Conference. Correspondents include Newton Diehl Baker, Bernard M. Baruch, Tasker Howard Bliss, Louis Dembitz Brandeis, William Jennings Bryan, Albert Sidney Burleson, Bainbridge Colby, Josephus Daniels, Cleveland H. Dodge, Thomas Watt Gregory, Herbert Hoover, Edward Mandell House, David Franklin Houston, Franklin K. Lane, Robert Lansing, Walter Hines Page, Alexander Mitchell Palmer, William Cox Redfield, William H. Taft, Joseph P. Tumulty, Oscar Wilder Underwood, John Sharp Williams, and William Bauchop Wilson. Includes previously restricted correspondence (1915-1923) between President Wilson and his second wife, Edith Bolling Galt Wilson, as well as other family and personal papers of Mrs. Wilson.
Microfilm edition of Series 1-19 available
Microfilm produced from originals in the Manuscript Division.
Microfilm edition of selected lectures available
Microfilm edition of Providence journal available
Microfilm edition of J. A. Hoyt correspondence available
Microfilm edition of Wilson home manuscripts available
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Bliss, Tasker Howard, -- 1853-1930 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Burleson, Albert Sidney, -- 1863-1937 -- Correspondence; Colby, Bainbridge, -- 1869-1950 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Dodge, Cleveland H. -- 1860-1926 -- Correspondence; Gregory, Thomas Watt, -- 1861-1933 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Houston, David Franklin, -- 1866-1940 -- Correspondence; Lane, Franklin K. -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Page, Walter Hines, -- 1855-1918 -- Correspondence; Palmer, A. Mitchell -- 1872-1936 -- Correspondence; Redfield, William Cox, -- 1858-1932 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Tumulty, Joseph P. -- 1879-1954 -- Correspondence; Underwood, Oscar Wilder, -- 1862-1929 -- Correspondence; Williams, John Sharp, -- 1854-1932 -- Correspondence; Wilson, William Bauchop, -- 1862-1934 -- Correspondence; World War, 1914-1918 -- Peace; United States -- Politics and government -- 1913-1921.; Authors; Educators; Governors -- NewJersey; Lawyers; Presidents -- United States